Neural Responses During Emotion Transitions and Emotion Regulation - Hao, Yu; Yao, Lin; Evans, Gary W. (Frontiers in Psychology, 2021)
Why are some people more susceptible to interference from previous emotional stimuli? Neural mechanisms underlying emotion regulation are typically studied with one-off positive or negative stimuli. Less is known about how they operate during dynamic emotional experiences which more closely resemble how emotions occur in real life. Therefore, we investigated the interaction among temporal context, stimulus content, and regulatory strategy. Image sequences included either neutral to negative emotion or negative to neutral emotion. Participants were instructed to either passively watch the emotional stimuli or apply cognitive reappraisal during the image sequences presentation. Participants also reported their habitual use of cognitive reappraisal in their daily lives on a standard scale. We measured functional connectivity (FC) with EEG source localization. A three-way interaction suggested that in addition to momentary emotional content and regulatory effort, the temporal context of stimuli impacts FC of vmPFC-ACC in both alpha and beta frequency bands. In the reappraisal condition but not the passive watch conditions, individual differences in habitual reappraisal were manifested in the FC (vmPFC-ACC). In addition, habitual reappraisal did not moderate FC (vmPFC-ACC) in beta band and FC (vlPFC-PPC) in both bands. Emotion transitions may be more demanding because prefrontal-posterior FC in beta band decreased during emotion transitions regardless of emotional content or regulation efforts. Flexible emotion regulation enables the recruiting of neural activities in response to the content of dynamic, ever-changing experiences encountered in daily life.